Perbandingan Kejadian Anemia Pada Penggunaan Kontrasepsi Intra Uterine Device (Iud) Dan Suntik Kb 1 Bulan Di Desa Joho, Kecamatan Mojolaban, Kabupaten Sukoharjo, Jawa Tengah - Pradipta Harsatyo Kusworo (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2023)
The family planning policy implemented by the government in tackling the population makes women have to use contraception to reduce pregnancies. Use of contraceptives such as Intra Uterine Device (IUD) and 1 monthly KB injection can cause anemia. This study uses a comparative analysis and a pre-experimental one-shot case study approach. the target population is married women or couples and the actual population is mothers using intrauterine contraception devices (IUDs) and 1-month injectable birth control. With a sample requirement of 44 respondents. There is a difference in the incidence of anemia in the use of intrauterine device (IUD) contraception and 1-month contraceptive injection in Joho Village, Mojolaban District, Sukoharjo Regency, Central Java with the average hemoglobin level of 1-month contraceptive injection users being higher than IU users.